Pengaruh Strategi AMBT Terhadap Kemampuan Membaca Pemahaman Siswa Pada Mata Pelajaran Bahasa Indonesia - Imas Saadah; Dani Gunawan; Yennie Indriati Widyaningsih; Risma Nuriyanti (Institut Pendidikan Indonesia, 2023)
: This study aims to examine the effect of the AMBT strategy on students' reading comprehension skills in Indonesian subjects. This study uses a quantitative method of Quasi Experimental Design which is designed using a non-equivalent control group design. The subjects in this study were fourth grade students, totaling 40 students. Class IV A as the experimental group with a total of 20 students, and class IV B as a control group with a total of 20 students. Collecting data and instruments in this study used tests given before and after being given treatment. Data processing was carried out using a t-test with the help of Microsoft Excel 2016. The results of this study before being given treatment (pretest) showed the average reading comprehension ability of students was 61.62 and after being given treatment using the AMBT strategy, the average value was 80. .95. Based on the statistical results obtained tcount 2.874 and ttable 2.0373. Thus, it can be concluded that there is an effect of the AMBT strategy on students' reading comprehension skills in Indonesian class IV subjects at SDN 2 Banyuresmi.